Effects of fertigation strategies on water and nitrogen distribution under water storage pit irrigation for orchards - Li, Jingling; Chen, Pan; Sun, Xihuan; Liu, Ping (International Journal of Agricultural and Biological Engineering, 2018)
Water storage pit (WSP) irrigation is a simple and inexpensive technology suitable for orchards in semiarid and arid regions of North China. This study compared the effects of different fertigation strategies on water and nitrogen distribution, and ammonia volatilization. A fertigation experiment was conducted using a 30° wedge-shaped plexiglass soil container, which represents one-twelfth of the complete storage pit. The height of the container was 120 cm, and a plexiglass damper for simulating the zero flux plane of adjacent water storage pits was located at the 40 cm radius. Four fertigation strategies were used for WSP irrigation: solution application during the first half (N-W), the last half (W-N), the middle half of an irrigation cycle (W-N-W), and during the entire irrigation (N-N). Surface (SF) irrigation was used as a control treatment with solution application during the entire irrigation (SN-N). The experimental results showed that the soil water and ammonium contents at 0-10 cm soil depth under WSP irrigation were only 10.51% and 18.42% of those under SF irrigation, respectively. The cumulative NH3 volatilization under WSP irrigation was 51.71%-68.72% lower compared with that under SF irrigation. The soil water distributions were similar for all four fertigation strategies. NH3 volatilization mainly occurred at the pit wall interface, and cumulative NH3 volatilization loss followed the trend N-N > W-N > W-N-W > N-W. Ammonium was adsorbed into the soil and thus mostly remained near the pit wall. Low concentrations of ammonium were found near the edge of the wetting zone under all strategies. Compared to N-W, N-N and W-N-W treatments, W-N treatment decreased the nitrate accumulation at 80-90 cm by 38.6%, 19.0% and 10.3%, respectively. The W-N strategy was suggested for minimizing potential nitrate leaching.Keywords: water storage pit, fertigation, soil water, nitrogen distribution, orchards irrigationDOI: 10.25165/j.ijabe.20181101.3282Citation: Li J L, Chen P, Sun X H, Liu P. Effects of fertigation strategies on water and nitrogen distribution under water storage pit irrigation for orchards. Int J Agric & Biol Eng, 2018; 11(1): 165–171.